Pemikiran Islam Kontemporer Tentang Reposisi Kesetaraan Gender dalam Perspektif Al-Quran - Natardi Natardi; Ali Hamzah; Doli Witro (LPPM IAIN Parepare, 2020)
Gender is one of the many discourses that can be considered contemporary that attracts the attention of various groups ranging from adolescents, activists, academics, researchers, and government and even scholars. This discourse intends to close social injustice based on gender differences in order to realize the equality of men and women in their social aspects. Until now, gender discourse can be grouped into at least four parts, namely as a movement, as a philosophical discourse, the development of social issues into religious issues, and as an approach in religious studies. This paper will examine the perspective of gender equality understood by Muslim feminists. In general it can be mentioned that the purpose of feminist struggle is to realize the equality, dignity, and freedom of women in choosing and managing their lives, both inside and outside the household.